Continuity, coordination and cooperation as mediators between economic and non-economic satisfaction – a sales perspective - Høgevold, Nils M.; Svensson, Göran; Mostert, Pierre; Zietsman, Mariëtte L. (Journal of Business Economics and Management, 2020)
There is a gap in literature as to how multidimensional satisfaction fits into a nomological network with continuity, coordination and cooperation. Furthermore, most studies focusing on these constructs are limited to a buyer perspective. The objective of this study is to fill this gap by testing a model whereby continuity, coordination and cooperation are regarded as mediators between economic and non-economic satisfaction specifically within business-sales representative relationships, thereby establishing a foundation to assess the structural properties between economic satisfaction and non-economic satisfaction within a business sales context. Managerial implications offered in the paper were discussed and the practical relevance and implementation thereof validated by experienced sales directors. This study contributes by revealing that continuity, coordination and cooperation to some extent mediates separately as well as cumulatively the relationship between economic satisfaction and non-economic satisfaction within a business sales context. Subsequently, it contributes by extending our understanding in relation to existing theory and previous studies of business relationships to a business sales perspective.